The Campus Canopy, 1939-10-13 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1939)
The Campus Canopy, October 13, 1939. Vol. 6, No. 3. -- Regulations Are Announced Concerning Absences -- Citizenship Day Is Observed -- Tuesday Set For Initiation of New Sock And Buskiners -- Administration Grants Thanksgiving Holidays -- Home Going Weekend -- Students May Leave Campus After Last Class Before Lunch on Wednesday, Nov, 22 -- Freshmen And Sophomore Councils To Begin Activities -- Y. W. C. A. Vesper Choir Will be Composed Of Nineteen Singers -- Fine Arts Club Will Sponsor Programs -- Eleven New Members Elected To Philharmonic -- Lambdas And Kappas Vie For Freshman Talent -- French Club Reorganizes -- Evans Captivates G.S.W.C. With Crazy Monologues -- Social Calendar -- Reade Goes To Atlanta And Virginia
Digitized from original print, Valdosta State University Archives and Special Collections, December 2, 2016.
Keywords: The Campus Canopy; 1930s; 1939; The Georgia State Woman's College; GSWC; Valdosta State College; VSC; Valdosta State University; VSU